2009
DOI: 10.1111/j.1540-8159.2008.02287.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Blood Flow Produced by Muscle Contractions Induced by Intracardiac Electrical CPR during Ventricular Fibrillation

Abstract: Intracardiac applied electrical CPR produced observable skeletal muscle contractions, measurable pressure pulses, and coronary perfusion pressures similar to MCC during a brief episode of untreated VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…There have been encouraging results with so-called 'medium voltage' electrical therapies to generate cardiac output in spite of ongoing VF as seen with storm. 6 Medium voltage therapy may show promise for treating pulseless electrical activity (PEA). 7 Since the detection of PEA is not possible with a purely electrogram analysis, the addition of a reliable estimate of cardiac output is required.…”
Section: New Resultsmentioning
confidence: 99%
“…There have been encouraging results with so-called 'medium voltage' electrical therapies to generate cardiac output in spite of ongoing VF as seen with storm. 6 Medium voltage therapy may show promise for treating pulseless electrical activity (PEA). 7 Since the detection of PEA is not possible with a purely electrogram analysis, the addition of a reliable estimate of cardiac output is required.…”
Section: New Resultsmentioning
confidence: 99%
“…Chest compression and epinephrine are effective for PEA, whereas electrical defibrillation is not. Medium voltage therapy (MVT) has recently been attempted, where electrical stimulation by a cardiac device during ventricular fibrillation or PEA induces skeletal muscle contractions and maintains coronary blood flow in the same manner as chest compression [14,15]. Although this technique has not yet been put to practical use, it would appear to be well suited to cases such as the present one.…”
Section: Discussionmentioning
confidence: 99%
“…Prior experimental studies showed that trains of electric stimulation, called medium-voltage electric therapy, applied via transthoracic or intracardiac electrodes can augment coronary and cerebral perfusion during VF or PEA. 46,47 Although the mechanism remains unclear, it has been proposed that medium-voltage electric therapy causes thoracic (skeletal) and myocardial muscle contractions that promote blood flow much like mechanical chest compression. Two different pulse train protocols have been tested: a very short pulse width of 0.15 milliseconds delivered at 14 pulses per train and a long pulse width of 7.5 milliseconds at 7 pulses per train to induce thoracic (skeletal) and myocardial muscle contractions.…”
Section: Medium-voltage Electric Therapy For Peamentioning
confidence: 99%